Studi Kasus Kerusakan Bantalan dan Poros Akibat Getaran Berlebih pada Sistem Permesinan Kapal - Nainggolan, Sadrakh; Bestian Hasiholan Nainggolan, Sadrakh (Blueprint Journal, 2025)
The ship's machinery system has a central role in supporting shipping operations, both in terms of transporting logistics and passenger transportation services.Although designed with high accuracy standards to ensure maximum and optimal performance, this system is still at risk of technical problems, one of which is excessive vibration and noise. This kind of condition not only has an impact on the comfort and safety of the ship's crew, but can also be an early signal of potential damage to engine components.The purpose of this study is to evaluate the impact of excessive vibration on damage that occurs to bearing and shaft components in ship engine systems.The study was conducted through a case study approach on a ship engine unit that showed abnormal symptoms in the form of increased vibration levels. By conducting vibration measurements, visual inspection, and component condition analysis, it was found that bearing wear and shaft misalignment were the main causes of the disturbance. The evaluation results revealed that component imbalance and errors in the installation process were the main triggering factors for the increase in vibration levels, even exceeding the recommended threshold. This had a direct impact on the engine's operating temperature, decreased efficiency, and risked overall system damage. These findings emphasize the importance of regular vibration monitoring and the implementation of preventive maintenance to avoid more  serious damage to the ship's machinery system.